Coupled MRT Lattice Boltzmann Study of Electrokinetic Mixing of Power-Law Fluids in Microchannels with Heterogeneous Surface Potential (Advances in Applied Mathematics and Mechanics, 2021)
The electrokinetic mixing, as a powerful technique in microfluidic devices, iswidely used in many applications. In this study, a more general dynamic model, whichconsists of Poisson equation, Nernst-Planck equation and Navier-Stokes equations, isused to describe the electrokinetic mixing of non-Newtonian fluids in microchannels.Furthermore, a coupled multiple-relaxation-time (MRT) lattice Boltzmann (LB) frameworkis developed to solve this complicated multi-physics transport phenomenon. Innumerical simulations, we mainly consider the effects of the arrangement of nonuniformsurface potentials and the power-law index on the mixing efficiency and the volumetricflow rate. Numerical results show that the mixing efficiency and the volumetricflow rate of shear-thinning fluids are higher than that of shear-thickening fluids underthe same condition. It is also shown that for both types of fluids, there should be abalance between the mixing and liquid transport in electrokinetic microfluidics.